Equine herpesviruses: a roundtable discussion. (1st July 2019) - Ivens, Philip; Rendle, David; Kydd, Julia; Crabtree, James; Moore, Sarah; Neal, Huw; Knapp, Simon; Bryant, Neil; Newton, J Richard
Abstract : Foreword: There are nine different equid herpesviruses (EHVs). Five types (EHV-1 to EHV-5) infect the domestic horse, while EHV-6 to EHV-9 are associated with infections in wild equids including asses and zebra. This review focuses on the commonest and most important clinical pathogens, the alphaherpesviruses EHV-1 and 4. These are respiratory pathogens and are also responsible for abortion and neurological disease. Several aspects of the biology of these viruses makes their control challenging. In particular, latent infection and reactivation of infection under stress, with subsequent virus shedding, makes elimination of these viruses impossible. Biosecurity measures are important both for minimising the risk of an outbreak and for controlling any outbreak when it occurs. Recognition of the disease and confirmatory diagnosis are also important in order for appropriate biosecurity measures to be instigated. Vaccination in key demographic groups is also important to reduce severe clinical disease. Unfortunately many horse owners are unaware of EHV or the importance of biosecurity measures and vaccination for control.